Bacterial community in African catfish (Clarias gariepinus) recirculating aquaculture systems under different stocking densities - Clols-Fuentes, Júlia; Nguinkal, Julien A.; Unger, Patrick; Kreikemeyer, Bernd; Palm, Harry W. (Frontiers in Marine Science, 2023)
We assessed the influence of different Clarias gariepinus stocking densities in Recirculation Aquaculture Systems (RAS) on the water microbiome composition. Pathogenic bacteria inside the rearing environment were also investigated to provide information regarding the risk of infection associated with common fish farming practices. Molecular approaches (RT-PCR and Miseq Ilumina sequencing) targeting the V3-V4 16s rRNA hypervariable region were used to construct a library of Amplicon Sequence Variants (ASV) and assess microbes’ identification, abundance and diversity. Our results reveal differences in the microbiomes from tank inflow water, tank outflow water and sedimentation tank water among all systems (intensive, semi-intensive and extensive). The highest accumulative abundance of ASVs was observed in all samples from the semi-intensive system, and its bacterial community appeared to be closely related. High variability between phyla was observed in water samples from the extensive system, and Mycobacterium sp. was the predominant pathogenic group detected, specifically in sedimenter samples. Finally, also the intensive system showed low evenness between samples, where high abundance values were sampled in the sedimenter. However, pathogenic bacteria were mainly detected in water inflow and outflow samples, with Mycobacterium sp. and Edwardsiella sp. being the predominant genus. Possible influences of fish stocking density and oxygen levels on the microorganism’s community are discussed.